Proses Berpikir Logis Siswa Sekolah Dasar Bertipe Kecerdasan Logis Matematis dalam Memecahkan Masalah Matematika - Liska Yanti Pane; Kamid Kamid; Asrial Asrial (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2013)
This research aims to describe logical thinking process of a logical-mathematical intelligence student. We employ qualitative method to disclose the subject’s learning process. Data are collected by interview and modified think aloud methods. The results show that subject has capability to find and organize problems and data correctly. Subject describes conditions that are needed to do the steps of problem solving strategy. The steps are done systematically until the end of problem solving process.